Pengaruh Pengaturan Diri dan Efekasi Diri dalam Pembelajaran Online Mahasiswa - Saputri, Rahmawati Eka; Kusumawati, Indah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to identify the influence of self-regulation, self-effect in online learning of students of Muhammadiyah University Tangerang. The sample in this study was as many as 150 students from the Education Study Program in the Covid 19 learning period this year. Sampling using non-probability sampling method using convenience sampling approach. As a result of the study, there was an influence between self-control and online learning which was 68.34%, then between self-affectation and online learning gave a score of 58.34%, and self-control and self-effect together influenced online learning with a value of 70.34%. In conclusion, between the variables of self-control and self-effect that simultaneously give the strongest influence on online learning of students at the Faculty of Teacher Training and Education at the University of Muhammadiyah Tangerang. Keywords: Self-effect, Online Learning, Self-Management Strategy